Dengue Virus Envelope Dimer Epitope Monoclonal Antibodies Isolated from Dengue Patients Are Protective against Zika Virus - J. A. Swanstrom (American Society for Microbiology, 2016)
ABSTRACT Zika virus (ZIKV) is a mosquito-borne flavivirus responsible for thousands of cases of severe fetal malformations and neurological disease since its introduction to Brazil in 2013. Antibodies to flaviviruses can be protective, resulting in lifelong immunity to reinfection by homologous virus. However, cross-reactive antibodies can complicate flavivirus diagnostics and promote more severe disease, as noted after serial dengue virus (DENV) infections. The endemic circulation of DENV in South America and elsewhere raises concerns that preexisting flavivirus immunity may modulate ZIKV disease and transmission potential. Here, we report on the ability of human monoclonal antibodies and immune sera derived from dengue patients to neutralize contemporary epidemic ZIKV strains. We demonstrate that a class of human monoclonal antibodies isolated from DENV patients neutralizes ZIKV in cell culture and is protective in a lethal murine model. We also tested a large panel of convalescent-phase immune sera from humans exposed to primary and repeat DENV infection. Although ZIKV is most closely related to DENV compared to other human-pathogenic flaviviruses, most DENV immune sera (73%) failed to neutralize ZIKV, while others had low (50% effective concentration [EC50], <1:100 serum dilution; 18%) or moderate to high (EC50, >1:100 serum dilution; 9%) levels of cross-neutralizing antibodies. Our results establish that ZIKV and DENV share epitopes that are targeted by neutralizing, protective human antibodies. The availability of potently neutralizing human monoclonal antibodies provides an immunotherapeutic approach to control life-threatening ZIKV infection and also points to the possibility of repurposing DENV vaccines to induce cross-protective immunity to ZIKV. IMPORTANCE ZIKV is an emerging arbovirus that has been associated with severe neurological birth defects and fetal loss in pregnant women and Guillain-Barré syndrome in adults. Currently, there is no vaccine or therapeutic for ZIKV. The identification of a class of antibodies (envelope dimer epitope 1 [EDE1]) that potently neutralizes ZIKV in addition to all four DENV serotypes points to a potential immunotherapeutic to combat ZIKV. This is especially salient given the precedent of antibody therapy to treat pregnant women infected with other viruses associated with microcephaly, such as cytomegalovirus and rubella virus. Furthermore, the identification of a functionally conserved epitope between ZIKV and DENV raises the possibility that a vaccine may be able to elicit neutralizing antibodies against both viruses.